2023
DOI: 10.1002/ptr.7922
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Capsicum annuum supplementation on lipid profiles in adults with metabolic syndrome and related disorders: A systematic review and meta‐analysis of randomized controlled trials

Abstract: The electiveness of Capsicum annuum supplementation in controlling dyslipidemia in adults has been unclear. Therefore, this meta‐analysis focuses on the relationship between C. annuum supplementation and lipid profile in adults with metabolic syndrome (MetS) and related disorders. PubMed, Scopus, ISI Web of Science, and the Cochrane Library were searched up to March 2021. Only randomized controlled trials (RCTs) studying the administration of C. annuum compared to control on lipid markers in adults with MetS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Today, changes in lifestyle and the use of fast foods and high-fat foods have increased the prevalence of liver diseases worldwide [ 35 ]. According to global statistics, two million people die each year due to chronic liver disorders, and these conditions are responsible for 4% of all deaths [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Today, changes in lifestyle and the use of fast foods and high-fat foods have increased the prevalence of liver diseases worldwide [ 35 ]. According to global statistics, two million people die each year due to chronic liver disorders, and these conditions are responsible for 4% of all deaths [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A healthy weight and regular physical activity are pivotal for averting liver disease (Keating et al, 2012; Peng et al, 2011). In recent years, complementary medicine and herbal remedies with therapeutic benefits have become increasingly popular in this area (Bagherniya et al, 2018; Hadi et al, 2019; Hjazi, 2023; Yao et al, 2016). The efficacy of various herbal interventions, including turmeric (Mansour‐Ghanaei et al, 2019), green tea (Mansour‐Ghanaei et al, 2018), garlic (Rastkar et al, 2022), and ginger (Zhou et al, 2023) have been investigated and their beneficial effects have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the efforts of researchers, magnesium alloys have been modified to have improved corrosion and mechanical properties, making them suitable for bone repair [15]. As part of the bone fixation system, there may be several components, including a bone plate, bone pin, bone screw, and so forth, each of which plays a vital role during the healing process [16,17]. Magnesium stents are medical devices made from magnesium alloys and they are used for various vascular applications, particularly in cardiology [18].…”
Section: Introductionmentioning
confidence: 99%